Highly efficient heat dissipating rubber material and method for preparing the same
Patent Information
- Application Number
- CN202611377618.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-16
AI Technical Summary
但纯硅橡胶本征热导率较低,导热能力有限,无法满足高功率器件的散热需求,因此通常需引入无机导热填料进行复合改性以提升橡胶材料的热传导性能
首先,将盐酸多巴胺接枝在六方氮化硼表面制得改性氮化硼;将γ-甲基丙烯酰氧丙基三甲氧基硅烷水解,接枝在球形氧化铝上制得改性氧化铝;盐酸多巴胺在弱碱性缓冲体系中发生氧化自聚合反应,在氮化硼片层表面原位生成致密的聚多巴胺包覆层,强化填料与基体的界面结合,减小界面空隙,降低界面热阻,提升热传导效率;γ-甲基丙烯酰氧丙基三甲氧基硅烷上的碳碳双键可与加成型硅橡胶体系中的乙烯基、Si-H键共同参与铂催化氢化加成反应,将氧化铝填料共价接入硅橡胶交联网络,使氧化铝与基体界面无明显空隙,热量可通过化学键快速传递,大幅降低界面热阻;改性球形氧化铝作为主体骨架搭建三维导热通路,改性片状氮化硼填充间隙、连通导热断点,二者共同构建连续致密的球-片协同导热网络,从而赋予高效散热橡胶材料优良的散热性能。
Smart Images

Figure REF-OBJ-1788765417406-000001 
Figure REF-OBJ-1788765417406-000002 
Figure REF-OBJ-1788765417406-000003
Abstract
Description
Technical Field
[0001] This invention relates to the field of rubber preparation technology, specifically to a high-efficiency heat-dissipating rubber material and its preparation method. Background Technology
[0002] Silicone rubber possesses excellent electrical insulation, high and low temperature resistance, elasticity, flexibility, and interfacial adhesion. It can effectively fill the microscopic gaps between electrical components and heat dissipation modules, reducing interfacial contact thermal resistance, making it the most widely used flexible heat dissipation matrix material. However, pure silicone rubber has low intrinsic thermal conductivity and limited thermal conductivity, which cannot meet the heat dissipation requirements of high-power devices. Therefore, inorganic thermally conductive fillers are usually introduced for composite modification to improve the thermal conductivity of the rubber material.
[0003] Meanwhile, ordinary thermal silicone rubber can only conduct heat and cannot reflect the operating temperature of the device itself. Traditional external temperature sensors are limited by the internal space of electrical components, making it impossible to place sensors at every heat-generating point of the chip or module. This easily leads to the omission of small, localized overheating areas, making it impossible to accurately pinpoint the overheating location in a timely manner. By adding thermally chromatic heat dissipation materials, visual traces of temperature exceeding limits can be retained. During downtime maintenance, the faulty heat-generating point can be quickly located visually, significantly reducing maintenance costs and downtime.
[0004] In summary, existing commercial thermally conductive silicone rubbers need to evolve to meet the integrated "heat dissipation-early warning" application requirements of next-generation intelligent electronic devices for thermal management materials. Summary of the Invention
[0005] The purpose of this invention is to provide a high-efficiency heat-dissipating rubber material and its preparation method, so as to solve the problems existing in the prior art.
[0006] To solve the above-mentioned technical problems, the present invention provides the following solution: A high-efficiency heat-dissipating rubber material is prepared by mixing 29.6-30 parts of vinyl-terminated polydimethylsiloxane, 3.1-3.3 parts of side-chain methyl hydrogen-containing silicone oil, 0.047-0.049 parts of hydrogen-terminated silicone oil, 0.031-0.033 parts of 1-ethynylcyclohexanol, 45-55 parts of modified alumina, 6-10 parts of modified boron nitride, 8.5-8.7 parts of thermochromic microcapsules, and 0.31-0.33 parts of caster platinum catalyst, followed by degassing and plate vulcanization. The modified boron nitride is prepared by grafting dopamine hydrochloride onto the surface of hexagonal boron nitride; The modified alumina is prepared by hydrolyzing γ-methacryloxypropyltrimethoxysilane and grafting it onto spherical alumina. The thermochromic microcapsules are made by polymerizing melamine and formaldehyde and coating them onto the surface of crystal violet lactone, bisphenol A, and a phase change material core.
[0007] A method for preparing a high-efficiency heat-dissipating rubber material, the method comprising the following preparation steps: (1) Mix tris(hydroxymethyl)aminomethane and deionized water, adjust the pH to 8.5 with concentrated hydrochloric acid, prepare a buffer solution of 0.4~0.6 mol / L, dilute with deionized water 9~11 times, mix the diluted buffer solution with anhydrous ethanol at a volume ratio of (2.5~3.5):1, add 0.1~0.2 times the mass of anhydrous ethanol of hexagonal boron nitride, ultrasonically disperse at room temperature for 10~20 min, add 0.3~0.5 times the mass of hexagonal boron nitride of dopamine hydrochloride, stir at room temperature and in air atmosphere for 9~11 h, let stand to settle, filter, wash with deionized water and anhydrous ethanol 2~4 times respectively, and vacuum dry at 60~70℃ for 6~8 h to obtain modified boron nitride; (2) Mix spherical alumina and silane hydrolysate at a mass ratio of 1:(1.9~2.2), heat to 50~60℃, stir for 2.5~3.5h, sonicate for 20~40min, filter, wash with deionized water and anhydrous ethanol 2~4 times respectively, vacuum dry at 50~60℃ for 10~12h, grind through a 200-mesh sieve to obtain modified alumina; (3) Mix deionized water and sodium dodecylbenzenesulfonate at a mass ratio of 1:(0.005~0.007), heat to 80~90℃, add oil phase at 0.09~0.11 times the mass of deionized water, stir and emulsify for 10~20 min, cool to 65~75℃, add citric acid to adjust the pH of the system to 4.6~5, add melamine formaldehyde prepolymer at a uniform rate of 0.5~0.6 times the mass of deionized water within 40~50 min, continue stirring for 2.5~3.5 h, cool to room temperature, vacuum filter, wash 2~4 times with deionized water and anhydrous ethanol respectively, and vacuum dry at 40~50℃ for 10~12 h to obtain thermochromic microcapsules; (4) By mass, 29.6-30 parts of vinyl-terminated polydimethylsiloxane, 3.1-3.3 parts of side-chain methyl hydrogen-containing silicone oil, 0.047-0.049 parts of hydrogen-terminated silicone oil, and 0.031-0.033 parts of 1-ethynylcyclohexanol are mixed evenly and stirred at room temperature for 5-15 minutes. 45-55 parts of modified alumina and 6-10 parts of modified boron nitride are added and stirred for 8-10 minutes. 8.5-8.7 parts of thermochromic microcapsules are added and stirred for 4-5 minutes. 0.31-0.33 parts of catalyst are added and stirred for 2-3 minutes. The mixture is then transferred to a vacuum degassing device and vacuum degassed for 8-10 minutes. The mixture is then filled into a mold, vulcanized on a flat plate, and the mold is opened after depressurization and cooling to obtain a high-efficiency heat-dissipating rubber material.
[0008] As an optimization, the hexagonal boron nitride used in step (1) is of type BN-E, with a particle size of 3-5 μm and a tap density of 0.45 g / cm³. 3 Purchased from Qinghe County Chaotai Metal Materials Co., Ltd.
[0009] As an optimization, the preparation process of the silane hydrolysate in step (2) is as follows: deionized water and anhydrous ethanol are mixed evenly at a volume ratio of 1:(8.5~9.5), γ-methacryloyloxypropyltrimethoxysilane is added at a mass ratio of 0.023~0.024 times that of deionized water, the pH of the solution is adjusted to 4~5 with glacial acetic acid, and the mixture is stirred at room temperature for 30~40 min to obtain the silane hydrolysate.
[0010] As an optimization, the alumina in step (2) is PAT spherical alumina with particle sizes of 2μm, 5μm, 10μm, 40μm and 70μm mixed and compounded in a mass ratio of 1:1:1:2:3, and purchased from Qinghe County Chaotai Metal Materials Co., Ltd.
[0011] As an optimization, the preparation process of the oil phase in step (3) is as follows: crystal violet lactone, bisphenol A and phase change material are mixed evenly in a mass ratio of 1:3:(40~60), heated to 80~90℃, and stirred for 10~20min to obtain the oil phase.
[0012] As an optimization, the phase change material can be one or a combination of several of hexadecyl alcohol, octadecyl alcohol, and methyl docosinate.
[0013] As an optimization, the preparation process of the melamine-formaldehyde prepolymer solution in step (3) is as follows: weigh melamine and formaldehyde at a molar ratio of 1:(2.9~3.1), add them to deionized water at a mass of 2.6~2.7 times that of formaldehyde, mix them evenly, adjust the pH of the system to 8~9 with 1mol / L sodium hydroxide aqueous solution, heat to 65~75℃, stir and react for 15~25min to obtain the melamine-formaldehyde prepolymer solution.
[0014] As an optimization, the viscosity of the terminal vinyl polydimethylsiloxane in step (4) is 10000 cSt and the vinyl content is 0.5 mol%; the viscosity of the side-chain methyl hydrogen-containing silicone oil is 80 cSt and the hydrogen content is 1 wt%; the viscosity of the terminal hydrogen silicone oil is 8 cSt and the hydrogen content is 0.205 wt%; the catalyst type is caster platinum catalyst; all were purchased from Jining Fangyu Chemical Co., Ltd.
[0015] As an optimization, the process parameters for the flat plate vulcanization in step (4) are: vulcanization at 75~85℃ and 13~15MPa for 35~45min.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are: First, modified boron nitride was prepared by grafting dopamine hydrochloride onto the surface of hexagonal boron nitride. Modified alumina was prepared by hydrolyzing γ-methacryloxypropyltrimethoxysilane and grafting it onto spherical alumina. Dopamine hydrochloride underwent oxidative self-polymerization in a weakly alkaline buffer system, forming a dense polydopamine coating layer in situ on the surface of the boron nitride sheets. This strengthened the interfacial bonding between the filler and the matrix, reduced interfacial porosity, lowered interfacial thermal resistance, and improved thermal conductivity. The carbon-carbon double bonds on γ-methacryloxypropyltrimethoxysilane can interact with... In addition-cure silicone rubber systems, vinyl groups and Si-H bonds participate in platinum-catalyzed hydrogenation addition reactions. Alumina filler is covalently incorporated into the silicone rubber crosslinking network, eliminating significant voids at the alumina-matrix interface. Heat can be rapidly transferred through chemical bonds, significantly reducing interfacial thermal resistance. Modified spherical alumina serves as the main framework to construct a three-dimensional thermal conduction pathway, while modified plate-shaped boron nitride fills the gaps and connects thermal conduction breaks. Together, they construct a continuous and dense sphere-plate synergistic thermal conduction network, thereby endowing the high-efficiency heat-dissipating rubber material with excellent heat dissipation performance.
[0017] Secondly, melamine and formaldehyde are polymerized and coated onto the surface of crystal violet lactone, bisphenol A, and a phase change material core to prepare thermochromic microcapsules. When the system temperature is below the melting point of the phase change material, the phase change solvent is a crystalline solid. The leuco dye crystal violet lactone and the color developer bisphenol A tightly aggregate in the solid medium. Bisphenol A acts as a proton donor, causing the lactone ring of crystal violet lactone to open, forming a conjugated quinone-type large π-bond structure, producing a stable charge-transfer complex that exhibits a characteristic blue-violet color. When the system temperature is above the melting point of the phase change material, the phase change solvent melts into a liquid state. Crystal violet lactone and bisphenol A are diluted and separated in a low-viscosity liquid medium. The charge-transfer complex dissociates, the lactone ring closes again, the conjugated structure is destroyed, and the color fades rapidly, appearing colorless or light-colored. The color change provides a direct indication of the temperature threshold and quickly locates local hot spots, thus giving the high-efficiency heat dissipation rubber material an excellent temperature visualization and early warning function. Meanwhile, by changing phase change solvents with different melting points, the color change warning temperature can be precisely controlled to adapt to the thermal management needs of electronic devices with different power levels and different operating temperature zones; or two phase change materials with different melting points can be compounded in proportion, and a continuously adjustable color change temperature between the two can be obtained based on the principle of melting point reduction, so as to realize customized warning for multiple temperature zones. Detailed Implementation
[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0019] Example 1:
[0020] A method for preparing a high-efficiency heat-dissipating rubber material, the method comprising the following steps: (1) Tris(hydroxymethyl)aminomethane and deionized water were mixed and the pH was adjusted to 8.5 with concentrated hydrochloric acid to prepare a 0.4 mol / L buffer solution. The buffer solution was diluted 9 times with deionized water. The diluted buffer solution was mixed with anhydrous ethanol at a volume ratio of 2.5:1. 0.1 times the mass of anhydrous ethanol was added and ultrasonically dispersed at room temperature for 20 min. 0.3 times the mass of hexagonal boron nitride was added and stirred at room temperature in an air atmosphere for 11 h. The mixture was allowed to settle, filtered, washed twice with deionized water and anhydrous ethanol, and vacuum dried at 60 °C for 8 h to obtain modified boron nitride. (2) Mix deionized water and anhydrous ethanol at a volume ratio of 1:8.5, add 0.023 times the mass of deionized water of γ-methacryloxypropyltrimethoxysilane, adjust the pH of the solution to 4 with glacial acetic acid, stir at room temperature for 40 min to obtain silane hydrolysate; mix spherical alumina and silane hydrolysate at a mass ratio of 1:1.9, heat to 50℃, stir for 3.5 h, sonicate for 40 min, filter, wash twice with deionized water and anhydrous ethanol respectively, vacuum dry at 50℃ for 12 h, grind through a 200 mesh sieve to obtain modified alumina; (3) Weigh melamine and formaldehyde in a molar ratio of 1:2.9, add them to 2.6 times the mass of formaldehyde in deionized water and mix well. Adjust the pH of the system to 8 with 1 mol / L sodium hydroxide aqueous solution, heat to 65℃, and stir for 25 min to obtain melamine-formaldehyde prepolymer solution; mix crystal violet lactone, bisphenol A, and octadecyl alcohol in a mass ratio of 1:3:40, heat to 80℃, and stir for 20 min to obtain oil phase; mix deionized water and sodium dodecylbenzenesulfonate in a mass ratio of 1:3:40. Mix the components at a ratio of 1:0.005 until homogeneous, heat to 80℃, add 0.09 times the mass of deionized water in the oil phase, stir and emulsify for 20 min, cool to 65℃, add citric acid to adjust the pH of the system to 4.6, add 0.5 times the mass of deionized water in the melamine-formaldehyde prepolymer solution at a uniform rate over 50 min, continue stirring for 3.5 h, cool to room temperature, vacuum filter, wash twice with deionized water and anhydrous ethanol respectively, and vacuum dry at 40℃ for 12 h to obtain thermochromic microcapsules; (4) By mass, 29.6 parts of vinyl-terminated polydimethylsiloxane, 3.1 parts of side-chain methyl hydrogen-containing silicone oil, 0.047 parts of hydrogen-terminated silicone oil, and 0.031 parts of 1-ethynylcyclohexanol were mixed evenly and stirred at room temperature for 15 min. 50 parts of modified alumina and 8 parts of modified boron nitride were added and stirred for another 10 min. 8.5 parts of thermochromic microcapsules were added and stirred for another 5 min. 0.31 parts of caster platinum catalyst were added and stirred for another 3 min. The mixture was transferred to a vacuum degassing device and vacuum degassed for 10 min. The mixture was then filled into a mold and vulcanized at 80℃ and 13MPa for 45 min. The pressure was released, the mold was cooled, and the mold was opened to obtain a high-efficiency heat-dissipating rubber material.
[0021] Example 2:
[0022] A method for preparing a high-efficiency heat-dissipating rubber material, the method comprising the following steps: (1) Tris(hydroxymethyl)aminomethane and deionized water were mixed and the pH was adjusted to 8.5 with concentrated hydrochloric acid to prepare a 0.5 mol / L buffer solution. The buffer solution was diluted 10 times with deionized water. The diluted buffer solution was mixed with anhydrous ethanol at a volume ratio of 3:1. 0.15 times the mass of anhydrous ethanol was added and ultrasonically dispersed at room temperature for 15 min. 0.4 times the mass of hexagonal boron nitride was added and stirred at room temperature in an air atmosphere for 10 h. The mixture was allowed to settle, filtered, washed 3 times with deionized water and anhydrous ethanol respectively, and vacuum dried at 65℃ for 7 h to obtain modified boron nitride. (2) Mix deionized water and anhydrous ethanol at a volume ratio of 1:9, add 0.02 times the mass of deionized water of γ-methacryloxypropyltrimethoxysilane, adjust the pH of the solution to 4.5 with glacial acetic acid, stir at room temperature for 35 min to obtain silane hydrolysate; mix spherical alumina and silane hydrolysate at a mass ratio of 1:2.05, heat to 55℃, stir for 3 h, sonicate for 30 min, filter, wash 3 times with deionized water and anhydrous ethanol respectively, vacuum dry at 55℃ for 11 h, grind through a 200 mesh sieve to obtain modified alumina; (3) Weigh melamine and formaldehyde in a molar ratio of 1:3, add them to 2.65 times the mass of formaldehyde in deionized water and mix well. Adjust the pH of the system to 8.5 with 1 mol / L sodium hydroxide aqueous solution, heat to 70℃, and stir for 20 min to obtain melamine-formaldehyde prepolymer solution; mix crystal violet lactone, bisphenol A, and octadecyl alcohol in a mass ratio of 1:3:50, heat to 85℃, and stir for 15 min to obtain oil phase; add deionized water and sodium dodecylbenzenesulfonate Mix the components evenly at a mass ratio of 1:0.01, heat to 85℃, add 0.1 times the mass of deionized water in the oil phase, stir and emulsify for 15 min, cool to 70℃, add citric acid to adjust the pH of the system to 4.8, add 0.55 times the mass of deionized water in the melamine-formaldehyde prepolymer solution at a uniform rate over 45 min, continue stirring for 3 h, cool to room temperature, vacuum filter, wash 3 times with deionized water and anhydrous ethanol respectively, and vacuum dry at 45℃ for 11 h to obtain thermochromic microcapsules; (4) By mass, 29.8 parts of vinyl-terminated polydimethylsiloxane, 3.2 parts of side-chain methyl hydrogen-containing silicone oil, 0.05 parts of hydrogen-terminated silicone oil, and 0.03 parts of 1-ethynylcyclohexanol were mixed evenly and stirred at room temperature for 10 min. 50 parts of modified alumina and 8 parts of modified boron nitride were added and stirred for another 9 min. 8.6 parts of thermochromic microcapsules were added and stirred for another 4.5 min. 0.32 parts of caster platinum catalyst were added and stirred for another 2.5 min. The mixture was then transferred to a vacuum degassing device and vacuum degassed for 9 min. The mixture was then filled into a mold and vulcanized at 80℃ and 14MPa for 40 min. The pressure was released, the mold was cooled, and the mold was opened to obtain a high-efficiency heat-dissipating rubber material.
[0023] Example 3:
[0024] A method for preparing a high-efficiency heat-dissipating rubber material, the method comprising the following steps: (1) Tris(hydroxymethyl)aminomethane and deionized water were mixed and the pH was adjusted to 8.5 with concentrated hydrochloric acid to prepare a buffer solution of 0.6 mol / L. The buffer solution was diluted 11 times with deionized water. The diluted buffer solution was mixed with anhydrous ethanol at a volume ratio of 3.5:1. 0.2 times the mass of anhydrous ethanol was added and ultrasonically dispersed at room temperature for 10 min. 0.5 times the mass of hexagonal boron nitride was added and stirred at room temperature in an air atmosphere for 9 h. The mixture was allowed to settle, filtered, washed 4 times with deionized water and anhydrous ethanol respectively, and vacuum dried at 70℃ for 6 h to obtain modified boron nitride. (2) Mix deionized water and anhydrous ethanol at a volume ratio of 1:9.5, add 0.024 times the mass of deionized water of γ-methacryloxypropyltrimethoxysilane, adjust the pH of the solution to 5 with glacial acetic acid, stir at room temperature for 30 min to obtain silane hydrolysate; mix spherical alumina and silane hydrolysate at a mass ratio of 1:2.2, heat to 60℃, stir for 2.5 h, sonicate for 20 min, filter, wash 4 times with deionized water and anhydrous ethanol respectively, vacuum dry at 60℃ for 10 h, grind through a 200 mesh sieve to obtain modified alumina; (3) Weigh melamine and formaldehyde in a molar ratio of 1:3.1, add them to 2.7 times the mass of formaldehyde in deionized water and mix well. Adjust the pH of the system to 9 with 1 mol / L sodium hydroxide aqueous solution, heat to 75℃, and stir for 15 min to obtain melamine-formaldehyde prepolymer solution; mix crystal violet lactone, bisphenol A, and octadecyl alcohol in a mass ratio of 1:3:60, heat to 90℃, and stir for 10 min to obtain oil phase; mix deionized water and sodium dodecylbenzene sulfonate in a molar ratio of 1:3:60. The mixture was thoroughly mixed at a mass ratio of 1:0.007, heated to 90℃, and 0.11 times the mass of deionized water was added to the oil phase. The mixture was stirred and emulsified for 10 min. The temperature was lowered to 75℃, and citric acid was added to adjust the pH of the system to 5. Melamine-formaldehyde prepolymer solution was added at a uniform rate over 40 min, and stirring was continued for 2.5 h. The mixture was cooled to room temperature, vacuum filtered, and washed 4 times with deionized water and anhydrous ethanol, respectively. The mixture was then vacuum dried at 50℃ for 10 h to obtain thermochromic microcapsules. (4) By mass, 30 parts of vinyl-terminated polydimethylsiloxane, 3.3 parts of side-chain methyl hydrogen-containing silicone oil, 0.049 parts of terminal hydrogen silicone oil, and 0.033 parts of 1-ethynylcyclohexanol were mixed evenly and stirred at room temperature for 5 min. 50 parts of modified alumina and 8 parts of modified boron nitride were added and stirred for another 8 min. 8.7 parts of thermochromic microcapsules were added and stirred for another 4 min. 0.33 parts of caster platinum catalyst were added and stirred for another 2 min. The mixture was transferred to a vacuum degassing device and vacuum degassed for 8 min. The mixture was then filled into a mold and vulcanized at 80℃ and 15MPa for 35 min. The pressure was released, the mold was cooled, and the mold was opened to obtain a high-efficiency heat-dissipating rubber material.
[0025] Comparative Example 1: The difference between the preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 1 and Example 2 is that modified alumina is not added in step (4). The remaining steps are the same as in Example 2.
[0026] Comparative Example 2: The difference between the preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 2 and Example 2 is that the amount of modified alumina added in step (4) is changed to 30 parts. The remaining steps are the same as in Example 2.
[0027] Comparative Example 3: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 3 differs from that in Example 2 in that the amount of modified alumina added in step (4) is changed to 40 parts. The remaining steps are the same as in Example 2.
[0028] Comparative Example 4: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 4 differs from that in Example 2 in that the amount of modified alumina added in step (4) is changed to 45 parts. The remaining steps are the same as in Example 2.
[0029] Comparative Example 5: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 5 differs from that in Example 2 in that the amount of modified alumina added in step (4) is changed to 55 parts. The remaining steps are the same as in Example 2.
[0030] Comparative Example 6: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 6 differs from that in Example 2 in that the amount of modified alumina added in step (4) is changed to 60 parts. The remaining steps are the same as in Example 2.
[0031] Comparative Example 7: The difference between the preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 7 and Example 2 is that modified boron nitride is not added in step (4). The remaining steps are the same as in Example 2.
[0032] Comparative Example 8: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 8 differs from that in Example 2 in that the amount of modified boron nitride added in step (4) is changed to 6 parts. The remaining steps are the same as in Example 2.
[0033] Comparative Example 9: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 9 differs from that in Example 2 in that the amount of modified boron nitride added in step (4) is changed to 7 parts. The remaining steps are the same as in Example 2.
[0034] Comparative Example 10: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 10 differs from that in Example 2 in that the amount of modified boron nitride added in step (4) is changed to 9 parts. The remaining steps are the same as in Example 2.
[0035] Comparative Example 11: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 11 differs from that in Example 2 in that the amount of modified boron nitride added in step (4) is changed to 10 parts. The remaining steps are the same as in Example 2.
[0036] Comparative Example 12: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 12 differs from that in Example 2 in that octadecyl alcohol in step (3) is replaced with hexadecyl alcohol. The remaining steps are the same as in Example 2.
[0037] Comparative Example 13: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 13 differs from that in Example 2 in that octadecyl alcohol in step (3) is replaced with methyl docosanoate. The remaining steps are the same as in Example 2.
[0038] Comparative Example 14: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 14 differs from that in Example 2 in that octadecyl alcohol in step (3) is replaced with paraffin. The remaining steps are the same as in Example 2.
[0039] Comparative Example 15: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 15 differs from that in Example 2 in that the vulcanization temperature in step (4) is changed to 60°C. The remaining steps are the same as in Example 2.
[0040] Comparative Example 16: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 16 differs from that in Example 2 in that the vulcanization temperature in step (4) is changed to 70°C. The remaining steps are the same as in Example 2.
[0041] Comparative Example 17: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 17 differs from that in Example 2 in that the vulcanization temperature in step (4) is changed to 75°C. The remaining steps are the same as in Example 2.
[0042] Comparative Example 18: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 18 differs from that in Example 2 in that the vulcanization temperature in step (4) is changed to 85°C. The remaining steps are the same as in Example 2.
[0043] Comparative Example 19: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 19 differs from that in Example 2 in that the vulcanization temperature in step (4) is changed to 90°C. The remaining steps are the same as in Example 2.
[0044] Comparative Example 20: The preparation method of the high-efficiency heat-dissipating rubber material in Comparative Example 20 differs from that in Example 2 in that the vulcanization temperature in step (4) is changed to 100°C. The remaining steps are the same as in Example 2.
[0045] Test Example 1 Test on the effect of inorganic filler addition amount on heat dissipation performance Test method: The high-efficiency heat-dissipating rubber materials of the examples and comparative examples were cut into circular samples with a diameter of 12.5 mm.
[0046] Thermal diffusivity test: According to GB / T 22588-2008, the thermal diffusivity α and density ρ of the sample were tested using a flash laser thermal conductivity meter. The results are shown in Table 1.
[0047] Specific heat capacity test: The specific heat capacity Cp of the sample was tested using a differential scanning calorimeter under high-purity nitrogen atmosphere at a gas flow rate of 20 mL / min and a heating rate of 10 °C / min. The results are shown in Table 1.
[0048] The thermal conductivity K = α·Cp·ρ was calculated. The results are shown in Table 1.
[0049] Table 1
[0050] Comparing the test results of Example 2 and Comparative Examples 1-11, it can be seen that adding modified alumina and modified boron nitride as inorganic fillers can form a continuous heat transfer path, generate a synergistic heat conduction effect, and significantly improve the thermal conductivity of the high-efficiency heat dissipation rubber material. However, excessive addition of inorganic fillers not only fails to improve thermal conductivity but also increases raw material costs and processing energy consumption. Therefore, the preferred amount of modified alumina added in this system is 50 parts, and the preferred amount of modified boron nitride added is 8 parts.
[0051] Test Example 2 Phase change material testing in thermochromic microcapsules Test Method: The high-efficiency heat-dissipating rubber materials of the examples and comparative examples were cut into standard samples of 3cm × 3cm and placed in a high and low temperature alternating test chamber. The initial colorimetric state b value of the samples was tested at 25℃ using a portable colorimeter. The temperature was increased from 25℃ to 70℃ at a rate of 5℃ / min, and the color change temperature and color change response time of the samples from blue disappearance were observed. Then, the temperature was decreased from 70℃ to 25℃ at a rate of 5℃ / min. This cycle was repeated 50 times, and the colorimetric state b value after 50 cycles was tested. 50 Value, calculate color retention rate = b / b 50 ×100%. The results are shown in Table 2.
[0052] Table 2
[0053] The test results of Comparative Examples 2 and 12-14 show that octadecyl alcohol, hexadecyl alcohol, and methyl docosanoate, as single pure substances, have sharp phase transition temperature points and rapid and clear color change processes, which can give high-efficiency heat dissipation rubber materials excellent temperature visualization and early warning functions. Furthermore, by changing the phase transition solvents with different melting points, the color change early warning temperature can be precisely controlled to meet the thermal management needs of electronic devices with different power levels and different operating temperature zones.
[0054] Test Example 3 Optimal vulcanization temperature test Test method: Shore hardness test: The high-efficiency heat-dissipating rubber materials of the examples and comparative examples were cut into standard specimens of 10mm×10mm×2mm, and the hardness of the specimens was tested using a Shore hardness tester. The results are shown in Table 3.
[0055] Mechanical property testing: The high-efficiency heat-dissipating rubber materials of the examples and comparative examples were cut into pieces of 75×4×2mm. 3 The dumbbell-shaped standard specimens were tested for mechanical properties using an electronic universal testing machine at a tensile rate of 20 mm / min. The results are shown in Table 3.
[0056] Color retention test after 50 cycles: Same as test example 2. Results are shown in Table 3.
[0057] Table 3
[0058] Comparative results from Examples 2 and 15-20 show that as the vulcanization temperature increases, the crosslinking density and Shore hardness of the high-efficiency heat-dissipating rubber material increase. The tensile strength exhibits a single-peak pattern of first increasing and then decreasing. This is because insufficient curing at low temperatures leads to an incomplete crosslinking network, resulting in lower strength. At high temperatures, over-crosslinking occurs, leading to uneven distribution of crosslinking points and the formation of internal pores, thus causing a decrease in tensile strength. Higher crosslinking levels result in less space for molecular chain movement and weaker elastic deformation, thus the elongation at break continuously decreases with increasing vulcanization temperature. When the vulcanization temperature exceeds 90°C, the melamine-formaldehyde shell softens and partially degrades due to heat, increasing the microcapsule breakage rate, increasing the risk of core material leakage, and significantly reducing the cycle color retention rate. Therefore, the preferred vulcanization temperature for this system is 80°C.
[0059] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A high-efficiency heat-dissipating rubber material, characterized in that, The high-efficiency heat-dissipating rubber material is prepared by mixing 29.6-30 parts of vinyl-terminated polydimethylsiloxane, 3.1-3.3 parts of side-chain methyl hydrogen-containing silicone oil, 0.047-0.049 parts of hydrogen-terminated silicone oil, 0.031-0.033 parts of 1-ethynylcyclohexanol, 45-55 parts of modified alumina, 6-10 parts of modified boron nitride, 8.5-8.7 parts of thermochromic microcapsules, and 0.31-0.33 parts of caster platinum catalyst, followed by degassing and plate vulcanization. The modified boron nitride is prepared by grafting dopamine hydrochloride onto the surface of hexagonal boron nitride; The modified alumina is prepared by hydrolyzing γ-methacryloxypropyltrimethoxysilane and grafting it onto spherical alumina. The thermochromic microcapsules are made by polymerizing melamine and formaldehyde and coating them onto the surface of crystal violet lactone, bisphenol A, and a phase change material core.
2. A method for preparing a high-efficiency heat-dissipating rubber material, characterized in that, The preparation method of the high-efficiency heat-dissipating rubber material includes the following preparation steps: (1) Mix tris(hydroxymethyl)aminomethane and deionized water, adjust the pH to 8.5 with concentrated hydrochloric acid, prepare a buffer solution of 0.4~0.6 mol / L, dilute with deionized water 9~11 times, mix the diluted buffer solution with anhydrous ethanol at a volume ratio of (2.5~3.5):1, add 0.1~0.2 times the mass of anhydrous ethanol of hexagonal boron nitride, disperse ultrasonically at room temperature, add 0.3~0.5 times the mass of hexagonal boron nitride of dopamine hydrochloride, stir at room temperature and in air atmosphere for 9~11 h, let stand to settle, filter, wash with deionized water and anhydrous ethanol, and vacuum dry to obtain modified boron nitride; (2) Mix spherical alumina and silane hydrolysate at a mass ratio of 1:(1.9~2.2), heat to 50~60℃, stir for 2.5~3.5h, sonicate, filter, wash with deionized water and anhydrous ethanol, vacuum dry, grind and sieve to obtain modified alumina; (3) Mix deionized water and sodium dodecylbenzenesulfonate at a mass ratio of 1:(0.005~0.007), heat to 80~90℃, add oil phase at 0.09~0.11 times the mass of deionized water, stir to emulsify, cool to 65~75℃, add citric acid to adjust the pH of the system to 4.6~5, add melamine formaldehyde prepolymer at a uniform rate of 0.5~0.6 times the mass of deionized water within 40~50min, continue stirring for 2.5~3.5h, cool to room temperature, vacuum filter, wash with deionized water and anhydrous ethanol, vacuum dry to obtain thermochromic microcapsules; (4) By mass, 29.6-30 parts of vinyl-terminated polydimethylsiloxane, 3.1-3.3 parts of side-chain methyl hydrogen-containing silicone oil, 0.047-0.049 parts of hydrogen-terminated silicone oil, and 0.031-0.033 parts of 1-ethynylcyclohexanol are mixed evenly and stirred at room temperature. 45-55 parts of modified alumina and 6-10 parts of modified boron nitride are added and stirred continuously. 8.5-8.7 parts of thermochromic microcapsules are added and stirred continuously. 0.31-0.33 parts of catalyst are added and stirred continuously. The mixture is transferred to a vacuum degassing device, degassed under vacuum, filled into a mold, vulcanized on a flat plate, depressurized, cooled, and opened to obtain a high-efficiency heat-dissipating rubber material.
3. The method for preparing the high-efficiency heat-dissipating rubber material according to claim 2, characterized in that, The hexagonal boron nitride used in step (1) is of type BN-E, with a particle size of 3-5 μm and a tap density of 0.45 g / cm³. 3 .
4. The method for preparing the high-efficiency heat-dissipating rubber material according to claim 2, characterized in that, The preparation process of the silane hydrolysate in step (2) is as follows: Deionized water and anhydrous ethanol are mixed evenly at a volume ratio of 1:(8.5~9.5), and γ-methacryloyloxypropyltrimethoxysilane is added at a mass ratio of 0.023~0.024 times that of deionized water. The pH of the solution is adjusted to 4~5 with glacial acetic acid, and the solution is stirred at room temperature for 30~40 min to obtain the silane hydrolysate.
5. The method for preparing the high-efficiency heat-dissipating rubber material according to claim 2, characterized in that, The alumina mentioned in step (2) is PAT spherical alumina with particle sizes of 2μm, 5μm, 10μm, 40μm and 70μm mixed and compounded in a mass ratio of 1:1:1:2:
3.
6. The method for preparing the high-efficiency heat-dissipating rubber material according to claim 2, characterized in that, The preparation process of the oil phase in step (3) is as follows: crystal violet lactone, bisphenol A and phase change material are mixed evenly in a mass ratio of 1:3:(40~60), heated to 80~90℃ and stirred for 10~20min to obtain the oil phase.
7. The method for preparing the high-efficiency heat-dissipating rubber material according to claim 6, characterized in that, The phase change material can be one or a combination of several of hexadecyl alcohol, octadecyl alcohol, and methyl docosinate.
8. The method for preparing the high-efficiency heat-dissipating rubber material according to claim 2, characterized in that, The preparation process of the melamine-formaldehyde prepolymer solution in step (3) is as follows: weigh melamine and formaldehyde at a molar ratio of 1:(2.9~3.1), add them to 2.6~2.7 times the mass of formaldehyde in deionized water and mix them evenly. Adjust the pH of the system to 8~9 with 1mol / L sodium hydroxide aqueous solution, heat to 65~75℃, stir and react for 15~25min to obtain the melamine-formaldehyde prepolymer solution.
9. The method for preparing the high-efficiency heat-dissipating rubber material according to claim 2, characterized in that, The viscosity of the terminal vinyl polydimethylsiloxane in step (4) is 10000 cSt and the vinyl content is 0.5 mol%; the viscosity of the side-chain methyl hydrogen-containing silicone oil is 80 cSt and the hydrogen content is 1 wt%; the viscosity of the terminal hydrogen-containing silicone oil is 8 cSt and the hydrogen content is 0.205 wt%; the catalyst type is caster platinum catalyst.
10. The method for preparing the high-efficiency heat-dissipating rubber material according to claim 2, characterized in that, The process parameters for the flat plate vulcanization in step (4) are: vulcanization at 75~85℃ and 13~15MPa for 35~45 minutes.